4E (energy, exergy, economic and environmental) investigation of LFR using MXene based silicone oil nanofluids. (February 2022) - Ghodbane, Mokhtar; Said, Zafar; Tiwari, Arun Kumar; Syam Sundar, L.; Li, Changhe; Boumeddane, Boussad
Graphical abstract: Highlights: MXene (Ti3 C2 ) based silicone oil as a working fluid for LFR system is used. With 0.1 wt%, the average LFR exergy efficiency is 12.21 % Best PEC value is obtained for the nano-oil with 0.1 wt%, where it improved by 15.50 % Total project cost reduction from 0.95 to 0.92 M$. The annual CO2 mitigation varies from 3.20 to 3.29-tons CO2 /year. Abstract: The study aims to conduct a numerical investigation of 4E (Energy-Exergy-Economic-Environmental) for an industrial process with linear Fresnel reflector (LFR) coupled with Therminol 66 oil storage tank conducted in the El-Oued region of Algeria. MXene (Ti3 C2 )/silicone oil nanofluid at various weight concentrations of 0.05%, 0.08%, and 0.1%, flowing in different industrial process centers coupled with LFR has been evaluated. Results show enhanced thermal conductivity of 22%, 40% and 64%, at 0.05, 0.08 and 0.1 wt% of silicone oil nanofluids at a temperature of 150 °C against the base fluid data. Nanofluid shows Newtonian fluid behavior with the examined shear rate. MATLAB code has been developed to solve the heat balance equations. Optical efficiency of LFR enhances to 60.42%, and highest LFR's efficiencies have been recorded for 0.1 wt% of MXene/silicone oil nanofluid with an average thermal efficiency of 58.07%, exergy efficiency of 12.21%, and performance evaluation criteria of 15.50 %. Using 0.1 wt% of nanofluid in LFR system reduced its cost from 0.95 M$ to 0.92 M$. From energy, and exergy point of view, 3.29 Tons CO2 /year, and 0.663 Ton CO2 /year were reduced, respectively. Maximum overall annual energy and exergy gain is 47.67 $/year and 9.61 $/year, respectively.